Tirto.id’s Critical Construction against Government’s Unreadiness in Handling Covid-19 - Hendra Alfani; Budi Santoso; Lishapsari Prihatini (Komunikator, 2021)
Mass media as the main channel of information was responsible for conveying information that became the public reference. Tirto.id, a verified news portal at the Press Council, reported six investigative news stories high lighting the government’s unpreparedness in dealing with the spread of Covid-19. The news between 27 February to 14 March 2020 were the objects of this research. Based on the objects, this research focused on the construction of Tirto.id on the reality of the government’s unpreparedness. This study used a descriptive qualitative method through Robert M. Entman’s framing analysis model. The reports of this study werestructured into: Define Problems, Diagnose Causes, Make Moral Judgments, and Treatment Recommendations. On the aspect of Define Problems, the research showed misinformation and coordination. The aspects of DiagnoseCauses were being ignored because of safe feeling. On the aspect of Make Moral Judgments, it showed criticism of biased policies. Meanwhile, on Treatment Recommendations, the state/government must be able to protect its people. The conclusion obtained showed that Tirto.id saw the government’s unpreparedness as a reflection of the country’s failure to protect its people due to unprofessional actions and biased policies in handling Covid-19.